Synergistic Ice Inhibition Effect Enhances Rapid Freezing Cryopreservation with Low Concentration of Cryoprotectants - Chang, Tie (Adv Sci (Weinh), 2021)
Despite recent advances in controlling ice formation and growth, it remains a challenge to design anti‐icing materials in various fields from atmospheric to biological cryopreservation. Herein, tungsten diselenide (WSe(2))‐polyvinyl pyrrolidone (PVP) nanoparticles (NPs) are synthesized through one‐step solvothermal route. The WSe(2)‐PVP NPs show synergetic ice regulation ability both in the freezing and thawing processes. Molecularly speaking, PVP containing amides group can form hydrogen bonds with water molecules. At a macro level, the WSe(2)‐PVP NPs show adsorption‐inhibition and photothermal conversation effects to synergistically restrict ice growth. Meanwhile, WSe(2)‐PVP NPs are for the first time used for the cryopreservation of human umbilical vein endothelial cell (HUVEC)‐laden constructs based on rapid freezing with low concentrations of cryoprotectants (CPAs), the experimental results indicate that a minimal concentration (0.5 mg mL(−1)) of WSe(2)‐PVP NPs can increase the viabilities of HUVECs in the constructs post cryopreservation (from 55.8% to 83.4%) and the cryopreserved constructs can also keep good condition in vivo within 7 days. Therefore, this work provides a novel strategy to synergistically suppress the formation and growth of the ice crystalsfor the cryopreservation of cells, tissues, or organs.